Efficiency of competitive training of triathletes at the annual stages of training of the training group - Rakhimova, Z. (Mental Enlightenment Scientific-Methodological Journal, 2024)
To improve the physical fitness of triathletes, the important factors in achieving high results of athletes are the correct selection of training equipment, proper distribution of power on the distance, and improvement of endurance performance. This means regular improvement of the quality and efficiency of physical training in the training process. Taking this into account, the article describes a set of special and general training exercises for triathletes.